Highly selective and efficient adsorption dyes self-assembled by 3D hierarchical architecture of molybdenum oxide1. Issue 104 (11th November 2015) - Wang, Min; Song, Xiao-xiao; Cheng, Xiao-Li; Zhou, Xin; Zhang, Xian-fa; Cai, Zhuang; Xu, Ying-Ming; Gao, Shan; Zhao, Hui; Huo, Li-Hua
<x xml:space="preserve">Abstract</x> A novel hierarchical architecture of MoO3 exhibits a fast and selective adsorption to the organic pollutants.